Perspectives Regarding the Role of Biochanin A in Humans - Yu, Chen; Zhang, Peng; Lou, Lixin; Wang, Yang (Frontiers in Pharmacology, 2019)
Biochanin A (BCA) is an isoflavone mainly found in red clover with poor solubility and oral absorption that is known to have various effects, including anti-inflammatory, estrogen-like, and glucose and lipid metabolism modulatory activity as well as cancer preventive, neuroprotective and drug interaction effects. BCA is already commercially available and is among the main ingredients in many types of supplements used to alleviate postmenopausal symptoms in women. The activity of BCA has not been adequately evaluated in humans. However, the results of many in vitro and in vivo studies investigating the potential health benefits of BCA are available, and the complex mechanisms by which BCA modulates transcription, apoptosis, metabolism and immune responses have been revealed. Many efforts have been exerted to improve the poor bioavailability of BCA, and very promising results have been reported. This review focuses on the major effects of BCA and its possible molecular targets, potential uses, and limitations in health maintenance and treatment.